Biosecurity in beauty and aesthetic centers (Horizontes de Enfermería, 2018)
The present study was carried out in beauty centers of the city of Tulcán, province of Carchi. Its objective was to determine the level of knowledge about biosafety in the workers of the beauty centers and their applicability in the attention to the users. People who work in beauty salons and aesthetics have intimate contact with the skin, sick people and sometimes blood. Scissors, razors, tweezers and facial instruments sometimes result in cuts, which when contaminated must be disinfected or eliminated to avoid transmitting diseases to users. A descriptive, quali quantitative and field study was applied, using the survey as study techniques, in order to determine the level of knowledge about biosecurity in the workers of the beauty centers and the direct observation to determine the applicability of biosafety regulations in the establishment. As a result, 50% of the respondents were unaware of biosafety norms, 81.25% said they sometimes use gloves to perform cosmetic or capillary procedures, 68.75% have not received any type of training on protocols. of biosafety, 68.75% mentioned using the appropriate uniform at times. In addition, according to the data collected in the observation sheet, it was found that 31.25% of establishments do not have adequate containers for the disposal of sharps, 87.5% do not have containers for the disposal of infectious waste. 100% do not have containers for special waste and do not classify the waste correctly. In conclusion, it was possible to demonstrate that there is a high risk of transmission of diseases by the workers towards the users due to the low knowledge and applicability of biosafety norms.
Keywords: Biosecurity; beauty centers; knowledge; diseases